DEMOCRACY IN INDONESIA CONSTITUTIONAL LIFE - Bambang Panji Gunawan (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
Democracy is an ideal system of constitutional life and that comes from the West. Democracy implies power or government by the people, from the people and for the people. When the Western democracy is transformed into the non-West countries with different history and culture, democracy will take time to adjust to the situation, and subjects to various changes in the application in accordance with the new different environment. A frequent problem that emerges in the practice of democracy is how the government by the people, of the people and for the people is effectively implemented in constitutional practice. This paper provides thought concerned with the concept of democracy, including democratization in the development of constitutional practice. The methodology of this paper is normative law. The conclussion of this paper is there same democracy systems, democracy which is based on freedom and equality; democracy which is based on the progress in social and economic affairs; democracy which is based on freedom and equality, and on social and economic progress as well.